Sengketa Kewenangan Lembaga Negara - Febiana, Fina (Jurnal Ilmiah Wahana Pendidikan, 2024)
Resolving disputes about the jurisdiction of governmental entities assigned powers under the 1945 Constitution is an ongoing responsibility of the Constitutional Court. Even in constitutional law, the phrase "state institution" might mean different things to different people. insufficient knowledge on the state entities that would be vested with the power to resolve disputes regarding the jurisdiction of the Constitutional Court. Given that they are discussed broadly, there are more than two Indonesian state institutions. The difficulty of resolving disagreements regarding the institutional authority of the Constitutional Court is the primary focus of this paper. Legal normative and conceptual research are the methods utilized. The complexity of resolving authority disputes involving state institutions, particularly the concept of state institutions and the optimization of processes and their resolution, is illustrated by the discussion's conclusion. In this particular instance, it would appear that judges of the Constitutional Court have significantly more discretion over which state institutions and individuals may be challenged in cases involving the power of state institutions, the Constitutional Court's judges are authorized to differentiate between subjectum litis and objectum litis according to Regulation 08/PMK/2006.